Providing a Culturally Sensitive Approach to Support Indigenous Cancer Patients and Their Families: A Nurse Navigator’s Experience - Abdul-Fatah, Tara (Université d'Ottawa / University of Ottawa, 2019)
Cancer among Indigenous Peoples (First Nations, Inuit, and Métis) is disproportionately higher than the overall Canadian population. Many Indigenous Peoples have difficulty accessing care and do not receive culturally safe care due to a longstanding history of marginalization and colonization. The role of a nurse navigator (NN) was developed to improve continuity of care and overall health outcomes for Indigenous Peoples; however, limited research exists on what a NN does or how they are perceived. Using constructivist case study methodology, this thesis explored the experiences of a NN working in a large tertiary care hospital in Ontario, Canada, and the processes the NN used to support Indigenous cancer patients in a culturally safe manner. Six in-depth semi-structured interviews were performed with health care providers and managers, and shadowing of a NN occurred over two weeks allowing direct observations of the NN that was captured in field notes and reflective journaling. Interviews were audiotaped and transcribed; all data was entered into NVIVO 12 qualitative software and coded thematically. Analysis revealed the NN to be an important complement to clinical care and key resource to navigating the health care system, providing mechanisms for building trust, and raising awareness of Indigenous historical and cultural contexts. The NN practiced non-conventional, patient-centered approaches that included engaging with the land and arts, interpreting healthcare information, advocating for and aiding autonomy over healthcare. All participants felt the NN had a positive influence on health and wellbeing. Thesis results inform healthcare delivery and nursing practice to improve quality of care and outcomes for Indigenous cancer patients.
Keywords: Indigenous; Registered Nurse; Nurse Navigator; Canada; Case study; Cancer